2022
DOI: 10.18280/ts.390326
|View full text |Cite
|
Sign up to set email alerts
|

Android Device Malware Classification Framework Using Multistep Image Feature Extraction and Multihead Deep Neural Ensemble

Abstract: The incidence of malicious threats to computer systems has increased with the increasing use of Android devices and high-speed Internet. Malware visualization mechanism can analyze a computer whenever a software or system crash occurs because of malicious activity. This paper presents a new malware classification approach to recognize such Android device malware families by capturing suspicious processes in the form of different size color images. Important local and global characteristics of color images are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Many of these studies [16][17][18][19][20][21] provided their accuracy rates with the method they applied, but many of them either employed very limited datasets or did not share them. When comparing the work carried out in this study, no dataset was found other than the two datasets utilized throughout the study.…”
Section: Related Workmentioning
confidence: 99%
“…Many of these studies [16][17][18][19][20][21] provided their accuracy rates with the method they applied, but many of them either employed very limited datasets or did not share them. When comparing the work carried out in this study, no dataset was found other than the two datasets utilized throughout the study.…”
Section: Related Workmentioning
confidence: 99%